Student teachers' experiences of using photos in teacher reflection. Issue 1 (2nd January 2021) - Hahl, Kaisa
ABSTRACT: Teacher reflection is part of teacher education worldwide and often done through discussion or in writing. This study looks into student teachers' experiences of reflecting on the development of teacher identity through a photo reflection report instead of a traditional written report. The study examines student teachers' experiences of how a photo reflection report can help them consider their emerging teacher identity and developmental process as a teacher during their one year of pedagogical studies. The participants (n = 27) compiled a photo report with at least seven photos with text descriptions according to selected guiding questions. Data of participant experiences were collected through an online questionnaire at the end of a subject teacher education programme in Finland. The questionnaire data were analysed with thematic analysis. The findings show that the student teachers found the photo reflection report a meaningful and enjoyable way to consider their development as teachers. The photos helped to structure reflection and analyse different aspects of teacherhood. The photo report allowed sufficient flexibility and freedom to make the reflection personal and about one's own story, which was considered valuable.